The Prosperity Gospel: Debating Modernity in Africa and the African Diaspora - Kwateng-Yeboah, James (Journal of Africana Religions, 2021)
Debates over the role of Pentecostalism in effecting modernity through its widespread "prosperity gospel" remain inconclusive. Though Weber's Protestant Ethic has been persistently invoked, sociological analyses reveal that the prosperity gospel challenges dominant Weberian conceptualizations of modernity. On one hand, the doctrine refutes Weber's central claim of modern societies by its pervasive "enchantment." On the other hand, the prosperity gospel shares modern traits of human autonomy and entrepreneurship. Does the prosperity gospel demonstrate simultaneously modern and antimodern themes? Using cases from Africa and the African diaspora, this essay critically reviews how modernity has functioned as a complicated category for analyses of the prosperity gospel and for Pentecostalism. Showing that modernity is mediated irreducibly by the historical and cultural backgrounds of the society it encounters, the essay argues for the potency of the "multiple modernities" paradigm as an analytical framework that better captures realities of Africana contexts, notably Pentecostalism and the prosperity gospel.
paid